Landscape Heterogeneity and Island Identity as Drivers of Mesoscale Structure of Pollination Networks - Lazaros Neokosmidis; Yiannis G. Zevgolis; Panayiotis G. Dimitrakopoulos; Theodora Petanidou (Diversity)
Indirect interactions enforce ecological and evolutionary dynamics within pollination networks. An effective way to study overall indirect interactions in a network is through motif profiles, which represent the network’s mesoscale structure, as well as species’ structural roles, reflecting their participation in motifs. Here, we surveyed 37 pollination networks across eight Aegean islands, a region with a complex biogeographic history, to examine (a) whether species’ structural roles in pollination networks are determined by species, landscape, or island identity; (b) the impact of landscape heterogeneity and island identity on the mesoscale structure of pollination networks; and (c) the variation explained by landscape drivers and island identity in motif profiles compared to link composition. Using PERMANOVA, we found that all three factors significantly grouped species’ structural roles, indicating the combined influence of niche-based and neutral processes. Interestingly, using two dbRDA models to evaluate the combined effects of landscape context and island identity on motif profiles and network link compositions, we found that the first model explained 57% of the variance, whereas the second model accounted for only 16%. This finding emphasizes the potential of motif profiles in revealing interaction dynamics that might otherwise be overlooked. Furthermore, island identity significantly influenced all three responses, suggesting that regional island features play a key role in shaping local interactions.